Cross-file searching: how vendors help-and don't help-improve compatibility - Milstead, Jessica L (Searcher, 1999)
More producers have recognized the need to facilitate cross-file searching, at least of their own databases, and have begun to develop methods of improving consistency across their databases. The use of machine-aided or automatic indexing can have a major impact on cross-file vocabulary management. Sixteen vendors surveyed fall into the categories of: 1. complete cross-file compatibility, 2. high cross-file compatiblity, 3. moderate cross-file compatibility, and 4. limited cross-file compatibility.